Epineural adipose‐derived stem cell injection in a sciatic rodent model. Issue 7 (19th June 2018) - Kappos, Elisabeth A.; Baenziger‐Sieber, Patricia; Tremp, Mathias; Engels, Patricia E.; Thommen, Sarah; Sprenger, Lima; Benz, Robyn M.; Schaefer, Dirk J.; Schaeren, Stefan; Kalbermatten, Daniel Felix
Abstract: Background: The aim was to evaluate the regenerative effect of epineural injection of rat ASCs (rASCs) in three different settings of acute and chronic compression in a rat sciatic nerve model. Methods: Acute compression (60 s) with a vessel clamp over a distance of 1 mm (group 1) or 10 mm (group 2), as well as chronic compression with a permanent remaining, nonabsorbable polymeric clip over a distance of 1 mm (group 3) was performed. Depending on the group, either 5 × 10 6 rASCs or the same volume (25 μl) of culture medium (CM) was injected with a 30G needle in the epineurium at the time of compression. Outcome measures were functional gait evaluations, imaging analysis, histomorphometric analyses, and muscle weight. Results: The rats in group 2 had a better function than those with group 1 at one and especially at 2 weeks. After 4 weeks however, almost all rats were close to a normal function. There was a similar Muscle Weight Ratio (MWR) after 2 weeks in all groups, whereas after 4 weeks, the MWR in group 3 was lower compared with group 1 and 2. Histomorphometric analysis showed a better myelination in group 1 & 2 compared to group 3 after 4 weeks. ASCs have a beneficial effect on myelin thickness (G‐Ratio). Conclusions: We successfully evaluated the regenerative effect of epineural injection of rASCs in three different settings of acute and chronic compression. However, there were no significant differences in outcomes between the ASC‐treated groups and control groups. Abstract : Representative images on PKH26‐labeled rASCs 4 weeks after injection (red) (A). Representative images of semi‐thin osmium tetroxide‐p‐phenylenediamine‐stained cross sections (B‐D). (B) 40 x magnification of the proximal part of a normal nerve (control group). (C) 40 x magnification of a cross section of the proximal part 4 weeks after acute short trauma (D) 40 x magnification of a cross section of the distal part 4 weeks after acute short trauma.